Airflow distribution and turbulence analysis in the longitudinal direction of a Boeing 767 mockup cabin - Shehadi, Maher (Kansas State University, 2015)
This dissertation focuses on airflow distribution in the longitudinal direction of a wide-body mockup aircraft cabin, turbulence energy and dissipation rates, and the effect of thermal plumes, generated by passengers, on airflow distribution within the cabin. The mockup cabin utilized for this study mimics a Boeing 767 passenger cabin and includes 11 rows in the longitudinal direction with each row consisting of seven seats. Each seat is occupied by an inflatable manikin which is instrumented with a 10 meters long wire heater generating approximately 100 Watts of distributed sensible heat, representing heat load from a sedentary human being. In order to investigate the fluid dynamics characteristics of the airflow within the cabin, different experimental techniques were implemented. Smoke visualization was used to qualitatively visualize the general airflow pattern inside the cabin. A tracer gas composed mainly of carbon dioxide was used to track the airflow distribution inside the cabin. The tracer gas was released in several locations and then sampled at various locations throughout the mockup cabin. The release and sampling of the tracer gas allowed tracing the airflow inside the cabin using non dispersive infrared sensors. Combining results from different release-sampling scenarios gave better understanding of the chaotic and three-dimensional nature of the airflow behavior inside the cabin. Air speed and turbulence parameters were evaluated using omni-directional probes. Finally, the effect of the heat generated by the thermal manikins on the airflow behavior was investigated. The results from the airflow visualization and the tracer gas were complementary and showed that there were multiple air circulations along the length of the cabin. The dimension of the circulations were controlled by the minimum physical distance inside the cabin. The identified-isotropic turbulence were spread over the full width of the cabin in the front and middle sections of the cabin, whereas, multiple-smaller circulations were identified in the rear section. Cabin sections identified with high speed fluctuations were associated with higher turbulence kinetic energy levels and lower local dissipation rates. These sections served as driving forces to create the circulations identified in the tracer gas experiments. Furthermore, the heat generated by the thermal manikins was shown to significantly impact the behavior of the gaseous flow inside the cabin, the turbulence parameters, and speed fluctuations. Detailed uncertainty analysis was conducted to estimate the uncertainty limits for the measurements taken. The uncertainty estimates obtained for the tracer gas results ranged from ±14% for the test cases with the heated manikins to ±17% with the corresponding unheated manikins cases. The data uncertainty limits for the turbulence parameters were of higher levels due to limitations associated with the omni-directional probes used to measure the speed. With flow repeatability phenomena in same locations inside the mockup cabin during different days reaching up to ±10%, the uncertainty estimates were considered acceptable for these chaotic and highly random airflow conditions within the cabin.
Keywords: Aircraft cain contamination; Airflow distribution; Turbulence analysis; Thermal plumes; Isotpoic turbulence; Aerospace Engineering (0538); Engineering (0537); Mechanical Engineering (0548)